Glycine betaine increases salt tolerance in maize (Zea mays L.) by regulating Na+ homeostasis - Zhu, Mingyuan; Li, Qiuxia; Zhang, Yushi; Zhang, Mingcai; Li, Zhaohu (Frontiers in Plant Science, 2022)
Improving crop salt tolerance is an adaptive measure to climate change for meeting future food demands. Previous studies have reported that glycine betaine (GB) plays critical roles as an osmolyte in enhancing plant salt resistance. However, the mechanism underlying the GB regulating plant Na+ homeostasis during response to salinity is poorly understood. In this study, hydroponically cultured maize with 125 mM NaCl for inducing salinity stress was treated with 100 M GB. We found that treatment with GB improved the growth of maize plants under non-stressed (NS) and salinity-stressed (SS) conditions. Treatment with GB significantly maintained the properties of chlorophyll fluorescence, including Fv/Fm, PSII, and NPQ, and increased the activity of the antioxidant enzymes for mitigating salt-induced growth inhibition. Moreover, GB decreased the Na+/K+ ratio primarily by reducing the accumulation of Na+ in plants. The results of NMT tests further confirmed that GB increased Na+ efflux from roots under SS condition, and fluorescence imaging of cellular Na+ suggested that GB reduced the cellular allocation of Na+. GB additionally increased Na+ efflux in leaf protoplasts under SS condition, and treatment with sodium orthovanadate, a plasma membrane (PM) H+-ATPase inhibitor, significantly alleviated the positive effects of GB on Na+ efflux under salt stress. GB significantly improved the vacuolar activity of NHX but had no significant effects on the activity of V type H+-ATPases. In addition, GB significantly upregulated the expression of the PM H+-ATPase genes, ZmMHA2 and ZmMHA4, and the Na+/H+ antiporter gene, ZmNHX1. While, the V type H+-ATPases gene, ZmVP1, was not significantly regulated by GB. Altogether these results indicate that GB regulates cellular Na+ homeostasis by enhancing PM H+-ATPases gene transcription and protein activities to improve maize salt tolerance. This study provided an extended understanding of the functions of GB in plant responses to salinity, which can help the development of supportive measures using GB for obtaining high maize yield in saline conditions.